Metodología para definir alternativas de programación lineal. Parte I: utilización de un modelo de programación lineal - Bertolotti, María Isabel (1987)
The objective of this paper is to maximize a function of the value added of the Argentine fishery system, in order to provide alternatives for the management and development of the fishery sector.